2014
DOI: 10.1177/1350650114522779
|View full text |Cite
|
Sign up to set email alerts
|

Piston ring load carrying capacity: Influence of cross-hatching parameters

Abstract: This work studies the influence of the cross-hatching groove parameters on a model piston ring load carrying capacity. Over 2000 transient calculations were performed varying all parameters (groove depth, groove width, groove angle, and the distance between cross-overs) to obtain the average load carrying capacity.It is shown that the load carrying capacity results fall close to a single master curve when using the Á parameter that is a combination of the groove parameters. Finally, the influence of the starva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 14 publications
3
23
0
Order By: Relevance
“…The flat ring load-carrying capacity increases with the increase of groove depth and groove width ratio (Figure 8(b1) and (b2)), while the load-carrying capacity shows a reduction trend with the groove density ( Figure 8(b3)). Similar results have also been reported in Bouassida et al 11 and Biboulet et al 12 In all simulation cases with texture, with a fixed minimum oil film thickness, the load-carrying capacity of the high plateau roughness is higher, indicating that the plateau roughness provides a second source of load-carrying capacity independent of the ring profile. Table 2 shows the simulation results without texture for nonflat ring with barrel height of 4 mm under steadystate conditions.…”
Section: Steady-state Conditionssupporting
confidence: 88%
See 2 more Smart Citations
“…The flat ring load-carrying capacity increases with the increase of groove depth and groove width ratio (Figure 8(b1) and (b2)), while the load-carrying capacity shows a reduction trend with the groove density ( Figure 8(b3)). Similar results have also been reported in Bouassida et al 11 and Biboulet et al 12 In all simulation cases with texture, with a fixed minimum oil film thickness, the load-carrying capacity of the high plateau roughness is higher, indicating that the plateau roughness provides a second source of load-carrying capacity independent of the ring profile. Table 2 shows the simulation results without texture for nonflat ring with barrel height of 4 mm under steadystate conditions.…”
Section: Steady-state Conditionssupporting
confidence: 88%
“…Moreover, this treatment has also been adopted in several previous publications 11,12,20,34 to study the cross-hatched texture on the liner. Their results showed that this assumption is effective to some extent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These large grooves may have a major contribution on the contact performance. The modeling of the groove influence is the main subject of Bouassida et al 13 Bouassida proposes a parameter to predict the load-carrying capacity as a function of operating conditions and groove geometry: groove depth, width, angle, and density. The main contribution of this paper is to describe the cylinder liner surface texture as a collection of grooves with identified geometry.…”
Section: Micro-geometrymentioning
confidence: 99%
“…Two types of data are extracted: the groove statistics (number of grooves and their geometry) and the plateau roughness. These data are useful to quantify the cross-hatched micro-geometry as descriptive parameters, but they will be used in the future as input data for lubricated contact calculations (Bouassida et al 13 ). Figure 2 shows a surface before and after identification.…”
Section: Cross-hatched Surface Identificationmentioning
confidence: 99%